The Concept Of Riba In Contemporary Business (Maaliyah Fiqh Study) - Kurniawan, Ade; Putra, Dede Satria; Fathurohman, Wahid; Burhanudin, Mohammad Siyam; Syarifudin, Amir; Ulwan, Abdullah Nasih; Yusuf, Muhammad Azmi; Al-Hammam, Ridho Royyan; Al Qaida, Muhammad; Nurrohim, Ahmad (Jurnal Sosial Sains dan Komunikasi, 2024)
Riba etymologically means increasing (al-ziyadah), growing (an-numuw), increasing (al-'uluw). Terminologically, riba is an addition to the principal of a debt that is agreed or required as compensation for the debt repayment period. Riba is absolutely, firmly and clearly haram according to the Qur'an, hadith and the consensus of the ulama. In general, riba is divided into two types, namely riba duyun/qardh (riba in debts) and riba buyu' (riba in buying and selling). Maqashid (purpose) of prohibiting riba: 1) to avoid tyrannical practices against business people; 2) violates the principle of the basic nature of loans/debts as social good transactions which are converted into business-motivated transactions; 3) prevent injustice committed by creditors against debtors by exploiting the interest on the debt; 4) avoid gharar in exchange/buying and selling; and 5) so that money does not become a commodity that is bought and sold. The criteria for riba qardh are prohibited when additional debt is agreed upon in the contract or the gift/addition is paid before the debt is repaid. As for riba buyu', it occurs when the two rules of riba buying and selling are violated, the exchange of similar ribawi goods must meet the same criteria of quality and quantity, and must be in cash. If the exchange is of a different type then the terms must be cash and you can set a margin in it. In practice, riba qardh often occurs in fintech products, insurance, capital markets, conventional banking and derivative businesses. The practice of riba buyu' occurs in foreign exchange transactions, in the exchange of similar money which is widespread online.